Edukasi Pengelolaan Sampah Guna Meningkatkan Pelestarian Lingkungan pada Siswa SMU Al-Huda Cengkareng-Jakarta - Muhammad Isradi; Hermanto Dwiatmoko; Hendy Yusman Firdaus; Elhazri Hasdian; Heru Andraiko; Agyanata Tua Munthe; Kukuh Mahi Sudrajat; Syafwandi Syafwandi (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Waste from various human activities is a common environmental problem that affects both the environment and human health. Managing and sorting waste based on type will make it easier to choose the next processing step, which will help reduce it. AL-HUDA Cengkareng High School is one of the educational units with a high school level in Cengkareng, West Jakarta, which has quite a lot of students. This school is under the Ministry of Education and Culture. The purpose of this activity is to increase students' understanding of waste management and sorting. The method used was to provide material and hands-on practice on how to process Takakura Home Method compost, divide students into small groups, and provide hands-on practice on how to make and process Takakura Home Method compost. As a result of this activity, students understand information about the types of waste, their definition, effects, types, and management, which makes them useful materials.